2020
DOI: 10.1021/acs.joc.0c01600
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Disulfide-Rich Peptides with Orthogonal Disulfide Pairing Motifs

Abstract: Disulfide-rich peptides (DRPs) are a class of peptides that are constrained through two or more disulfide bonds. Though natural DRPs have been extensively exploited for developing protein binders or potential therapeutics, their synthesis and re-engineering to bind new targets are not straightforward due to difficulties in handling the disulfide pairing problem. Rationally designed DRPs with an intrinsically orthogonal disulfide pairing propensity provide an alternative to the natural scaffolds for developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…A trade-off of soluble-support-assisted electrochemical peptide modification is that the strategy may be less likely to be compatible with larger or more hydrophilic targets. Nevertheless, the oxidation of cysteine residues clearly demonstrates the utility of electrochemistry for direct modification of native polypeptides and may prove useful as an orthogonal strategy for the synthesis of disulfide-rich RiPPs. , …”
Section: Direct Electrochemical Modification Of Peptides and Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…A trade-off of soluble-support-assisted electrochemical peptide modification is that the strategy may be less likely to be compatible with larger or more hydrophilic targets. Nevertheless, the oxidation of cysteine residues clearly demonstrates the utility of electrochemistry for direct modification of native polypeptides and may prove useful as an orthogonal strategy for the synthesis of disulfide-rich RiPPs. , …”
Section: Direct Electrochemical Modification Of Peptides and Proteinsmentioning
confidence: 99%
“…Nevertheless, the oxidation of cysteine residues clearly demonstrates the utility of electrochemistry for direct modification of native polypeptides and may prove useful as an orthogonal strategy for the synthesis of disulfide-rich RiPPs. 154,155 Future work may therefore focus on the electrochemical construction of complex disulfide architectures in which selective electrochemical disulfide formation in systems containing more than two free thiols might arise from discrete cysteine microenvironments. Given the wealth of existing cysteine modification approaches, including recent, highly enabling metal-catalyzed 156−159 and photochemical 135,160,161 methods, leveraging electrochemistry as a complementary platform for cysteine modification may ultimately require a broader understanding of the capacity for site-selectivity (e.g., stemming from predictable interactions with the electrode surface).…”
Section: ■ Direct Electrochemical Modification Of Peptides and Proteinsmentioning
confidence: 99%
“…Thus, these DRPs are essentially more tolerant to extensive sequence manipulations compared to the natural DRPs. However, the C/Pen-directed peptide folding relies on the incorporation of at least one or a pair of the 11-atom bisthiol motifs (i.e., CXPen and PenXC motifs; Figure a) into peptide chains. ,, The conservativeness of the bisthiol motifs significantly hampers the diversity of multicyclic structures that can be designed for C/Pen pattern-based DRPs. Moreover, ribosomal expression of these DRPs is challenging because two or more Pen residues have to be incorporated into sequences to construct the unique bisthiol motifs, thus hampering the applicability of these DRPs.…”
Section: Introductionmentioning
confidence: 99%
“…Protection and deprotection of cysteine thiol groups in peptides are critical steps in the synthesis of their disulfide derivatives, materials of considerable therapeutic interest. Two widely employed protection groups are acetamidomethyl (Acm) and 1,3-thiazolidine-4-carbonyl (Thz), for which transition metals have proved particularly useful in their removal prior to disulfide formation. Most of the known methods of deprotection suffer from various disadvantages, but we have recently shown that Pt­(IV) complexes offer considerable promise not only for efficient and rapid deprotection but also for the subsequent oxidation of the released thiol.…”
Section: Introductionmentioning
confidence: 99%